Bioprospecting medicinal plants of Centhini: Javanese ancient manuscript - Nafayu, Yulia Helvi Dwi; Kintoko, Kintoko; Pratama, Antonius Nugraha Widhi; Josafat, Anom; Raharjo, Angga Mardro; Triatmoko, Bawon; Nawiyanto, Nawiyanto; Wangchuk, Phurpa; Keller, Paul A.; Nugraha, Ari Satia (Ethnobotany Research and Applications, 2025)
Background: The inhabitants of Java-Indonesia have been developing a distinct culture for thousands of years. The resulting principles were depicted in Serat Centhini, a literary treasure of Javanese culture comprising values from spirituality to medicine centuries ago. There has been no comprehensive study regarding the potency of medicinal plants listed in this ancient book. Methods: Information was gathered from medicinal plants and diseases that were reported in the book. These were categorized by indications/traditional uses of the plants, and then the literature was reviewed for scientifically based evidence for their biological activities. Results: A total of 82 medicinal plants were described to treat twelve diseases, in which 32 species were previously reported to possess pharmacological potency relevant to their traditional claims. For example, 6-gingerol and zingerone from Z. officinale were demonstrated as erectile agents by testing in animals. Constituents of B. rotunda and Z. montanum (pinostrobin, boesenbergin A, zerumbone) indicated strong anti-ulcer activity based on an in vivo model. Cubebin from P. cubeba reduced AChE activity, with it’s potency being related to its use in Alzheimer therapy. Despite these reports, there are large research gaps, with reported activities based on crude extracts rather than single compounds. This requires extensive additional research to establish the active constituents and to clarify their mechanism of action. Conclusions: Serat Centhini reports medicinal plants with high potency, with the traditional knowledge of the Javanese people surviving the history of Indonesia. This knowledge can be used to expand the local pharmacopeia. Keywords: Serat Centhini; Javanese; Medicinal plants; Bioprospecting.